Speak for yourself a dynamic vocal workout - Moreau, Josept; Kebow, Ken; Theatre Art Video Library (Leucadia, CA : Theatre Arts Video Library, 1988)
The video is a comprehensive vocal and physical warm-up routine for the business and professional person. Using stretches from yoga, modern dance and the martial arts, accompanyied by easy vocalization, the warm-up is intended to relax the body while centering the breath and the voice.
Executive producer, Ron Ranson Jr. ; script, Susan Leigh
Narrator: Susan Leigh
Keywords: Voice culture -- Exercise